Cervical cancer incidence in the Siberian Federal District - L. D. Zhuikova; I. N. Odintsova; О. A. Ananina; L. V. Pikalova; N. Р. Lyakhova (Опухоли женской репродуктивной системы)
Background. When planning preventive measures and providing specialized care, it is important to take into account the epidemiology of malignant neoplasms.Objective: to analyze the incidence of cervical cancer in 10 territories of the Siberian Federal District.Materials and methods. Based on the data of the Federal State Statistics Service, the incidence of cervical cancer and the quality of cancer care were analyzed in 10 cancer centers for the years 2005–2019. Results. During the study period, an increase in the incidence of cervical cancer was observed in the Siberian Federal District. The maximum increase in the incidence rate was observed in most territories of the Tyva Republic (102.3 %). The decrease in the incidence rate was recorded in the Altai Republic (–15.4 %) and Tomsk Oblast (–14.3 %). The age-specific incidence rates were stable in patients aged 65 years and older, and a 1.4-fold increase was observed in women of the reproductive age (20–44 years). The highest incidence rates were observed in the age groups 35–39 years (37.8 %) and 40–44 years (42.0 %). The improvement in the rates of quality of cancer care indicated the high proportion of morphologically verified cancers, early cancer detection and high proportion of patients who were followed up for 5 years or more. The rates of late-stage cervical cancer and one-year mortality remain high.Conclusions. From 2004 to 2019, an increase in the incidence of cervical cancer was observed in the female population of the Siberian Federal District. The highest risk of cervical cancer was observed in women of the reproductive age (20–44 years). It is necessary to develop and organize anti-cancer measures to improve cancer care